Pengaruh Profitabilitas Dan Kebijakan Dividen Terhadap Nilai Perusahaan Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2020-2023 - Boris; Zalviwan, Muhammad; Indra Maulana, Uray Andrey (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2025)
This study analyzes the impact of profitability and dividend policy on the firm value of property and real estate companies listed on the Indonesia Stock Exchange (BEI) for the period 2020-2023. Profitability is measured using Return on Equity (ROE), dividend policy using Dividend Payout Ratio (DPR), and firm value using Price to Book Value (PBV). The study employs a panel data regression method with financial report data from BEI, analyzed using E-Views. The research sample consists of 19 companies that consistently distributed dividends from a total population of 92 companies. The results show that profitability (ROE) has a negative and significant impact on firm value (PBV). Meanwhile, dividend policy (DPR) does not have a significant impact on firm value. However, simultaneously, profitability and dividend policy significantly influence firm value